ChemInform Abstract: Copper‐Catalyzed Synthesis of Trisubstituted Isoxazoles via a Cascade Cyclization—Migration Process. Issue 6 (20th February 2013) - Ueda, Masafumi; Sugita, Shoichi; Sato, Aoi; Miyoshi, Tetsuya; Miyata, Okiko
Abstract Heating of alkynyl oxime ethers (I) and (III) with Cu(OTf)2 allows a convenient and atom‐economical access to trisubstituted isoxazoles.